Direct-acting antiviral treatment significantly shaped the gut microbiota in chronic hepatitis C patients: a pilot study - Elsherbiny, Nahla M.; Kamal El-Din, Omnia M.; Hassan, Elham Ahmed; Hetta, Helal F.; Alatawy, Roba; Sayed Ali, Mostafa A.; Alanazi, Fawaz E.; Abdel-Maksoud, Mohamed S.; Aljohani, Hashim M.; Badary, Mohamed Saad; Mahran, Zienab Gaber; Kresha, Marwa Abo; et al. (Frontiers in Microbiology, 2025)
BackgroundChronic hepatitis C (CHC) can be effectively cured with direct-acting antivirals (DAAs), yet the impact of CHC on the gut microbiota remains controversial, with limited research on changes in patients who achieve a sustained virological response (SVR) versus those who relapse.AimTo investigate the impact of CHC on the gut microbiota and compare changes between patients who achieved SVR post-DAA treatment and those who relapsed.MethodsIn this case-control study, 60 stool samples were collected from CHC patients (20 untreated, 20 post-DAAs SVR, and 20 relapsed patients) and 20 healthy individuals. The V3–V4 regions of the 16S rRNA gene were sequenced using MiSeq to analyze bacterial diversity and composition.ResultsCompared with healthy participants, CHC patients presented significantly altered bacterial diversity. The microbial diversity of the SVR patients was similar to that of the controls (p = 0.45), whereas the microbial diversity of the relapsed patients was lower. The gut microbiota clearly clustered on the basis of disease status. Firmicutes were predominant in treated patients, whereas Bacteroidetes and Proteobacteria were enriched in the relapsed group. Compared with the other groups, the SVR group presented lower Actinobacteria and higher Cyanobacteria levels. Genus-level analysis revealed significant disease-dependent biomarkers and intermicrobial coexistence. Prevotella, Bifidobacterium, and Lactobacillus were more prevalent in relapsed patients, whereas Bacteroides, Agathobacter, and Parabacteroides were more abundant in controls. Elusimicrobium, Christensenellaceae R-7, Catenibacterium, Oceanobacillus, and Candidatus Melainabacteria were significantly more abundant in the SVR group.ConclusionDAAs have a significant impact on the gut microbiota in CHC patients, resulting in distinct microbial patterns, biomarkers, and interactions. Successful HCV eradication restores bacterial diversity and reestablishes microbial communities resembling those in healthy individuals.